PENGARUH LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION DI SHOPEE MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING - Nadhifah Efendi; Retna Ngesti Sedyati; Prima Ratna Sari (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The focus of this study is to determine the effect of live streaming on purchase intention, the effect of purchase intention on purchase decisions, and the effect of live streaming on purchase decisions through purchase intention as an intervening variable on Gen Z Shopee users in Jember Regency using the Stimulus-Organism-Response (S-O-R) theory approach. This study applies a quantitative method with an explanatory type to 141 respondents selected using purposive sampling. A Likert scale questionnaire was used to collect data. Structural Equation Modeling based on Partial Least Squares (SEM-PLS) using SmartPLS 4 to analyze the data. The results show that live streaming has a positive and significant effect on purchase intention, purchase intention has a positive and significant effect on purchase decisions, and live streaming has a positive and significant effect on purchase decisions through purchase intention as an intervening variable. The conclusion of the study shows that effective live streaming can increase purchase intention, thereby strengthening the decision to purchase fashion products on Shopee. The managerial implication of this study is that sellers on Shopee need to optimize the quality of live streaming in order to increase purchase intention and encourage consumer purchasing decisions.